The Effects of Endocrine Therapies on Lipid Profiles in Chinese Young Women With Early Breast Cancer - Kang, Yi-Kun; Wang, Xue; Hu, Nan-Lin; Yue, Jian; Si, Yi-Ran; Ju, Jie; Gao, Song-Lin; Yuan, Peng (Frontiers in Oncology, 2021)
This study aimed to evaluate and compare the effects of various endocrine therapies on lipid profiles in young patients with breast cancer. A retrospective, single-center study was performed to investigate the effects of tamoxifen (TAM), tamoxifen plus ovarian function suppression (TAM+OFS), and aromatase inhibitors plus ovarian function suppression (AI+OFS) on lipid profiles during the 60 months of endocrine therapy in hormone receptor-positive patients aged <40 with early breast cancer. The primary endpoint was the cumulative incidence of lipid events, and the secondary endpoints were the changes in lipid profiles. A total of 230 young patients were included with the mean age of 35.7 years old. The patients in TAM group had significantly lower incidence of 5-year lipid events than those in TAM+OFS group (7.4% versus 21.3%; P=0.016) and AI+OFS group (7.4% versus 21.6%; P=0.009). The incidence of fatty liver was significantly higher in TAM+OFS group than TAM group (52.5%versus 30.9%; P=0.043). Lipid events were associated with younger age (odds ratio (OR)=0.865, 95% confidence interval (CI): 0.780-0960; P=0.006), higher baseline LDL-C (OR=14.959, 95% CI: 4.379-51.105; P<0.001), and use of OFS (OR=3.557, 95% CI: 1.151-10.989; P=0.027). At 60 months from initiation of endocrine therapy, highest LDL-C and TC, with lowest HDL-C level was detected in patients from AI+OFS group. Therefore, application of OFS, with younger age and higher baseline LDL-C, may increase the incidence of lipid events in premenopausal breast cancer. Therefore, more care should be taken for lipid profiles during the endocrine therapy for young breast cancer patients.